2020
DOI: 10.21149/10960
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening and socioeconomic disparities in Mexican older adults

Abstract: [No disponible]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The authors found that health insurance coverage, higher education and discussing reproductive issues with a health work-ers had the potential to be used as predictors of PSA screening; nonetheless, they emphasised that improved access to PSA screening may be accompanied by detrimental consequences [45]. A recent research study among elderly Mexican men showed that those who attended school had undergone PSA screenings more often than those who did not attended school, which can be explained by the better financial situation of educated people [46].…”
Section: Socioeconomic Status and Psa Screening Testmentioning
confidence: 99%
“…The authors found that health insurance coverage, higher education and discussing reproductive issues with a health work-ers had the potential to be used as predictors of PSA screening; nonetheless, they emphasised that improved access to PSA screening may be accompanied by detrimental consequences [45]. A recent research study among elderly Mexican men showed that those who attended school had undergone PSA screenings more often than those who did not attended school, which can be explained by the better financial situation of educated people [46].…”
Section: Socioeconomic Status and Psa Screening Testmentioning
confidence: 99%